Immobilization of Alkaline Collagenase from Bacillus subtilis onto Sulfonated Polystyrene Nanospheres for Hydrolysis of Tilapia Collagen - Ling Zhang; Xiaocui Yang; Kaijun Xiao; Yuyi Lu; Chunhai Li; Zijin Zhang (Journal of Food Quality)
The structure of an alkaline protease from Bacillus subtilis used by a tilapia collagen peptide manufacturer was analyzed, and the technology of the enzyme immobilized by sulfonated polystyrene (SPS) nanoparticles was studied. The particle size distribution, SEM, EDS, TEM, and FT-IR spectroscopy of the carrier before and after immobilization were analyzed. The results showed that the molecular weight of the purified enzyme protein was 31.0 kDa. The amino acid sequence with a consistency of 64.04% and one three-dimensional structure simulation diagram of the purified enzyme protein were obtained by LC-MS-MS, which suggested that the protein might belong to subtilisin. The optimal immobilization conditions were as follows: the volume ratio of the immobilization carrier to the enzyme was 3 : 50 (mL : mL), the immobilized temperature was 25°C, and the system pH was 4.5. Under this condition, the immobilization ratio of collagenase was 73.48%, the specific activity was 274.05 U/μg, and the specific activity of the immobilized enzyme was about 53.74% that of the free enzyme. The average particle size of SPS nanospheres was 155.1 nm. The characterization results of SEM, EDS, TEM, and FT-IR spectroscopy showed that the collagenase was successfully immobilized onto SPS nanospheres. The experimental results also showed that the collagenase could be immobilized effectively under the optimal conditions by using SPS nanospheres, and the operation process was simple, feasible, and of low cost with good prospect of industrial application.